STRATEGIES IN IMPROVING READING SKILLS OF UNIVERSITY ENGLISH LEARNERS - Alfian Alfian (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2019)
Studies on language learning strategies (LLS) have been conducted elsewhere in the world, however, there were very limited studies on student learning strategies in improving reading skills. Therefore, this study is aimed to identify the strategies used in improving reading skills. This case study was conducted by distributing questionaire involving 200 English Education and English Literature students as the sample of this study. The finding of this study demonstrated that the respondent use the LLS, such as memory, metacognitve, compensation, cognitive, affective, and social in improving reading skill. However, most of respondents reported to use metacognitive strategy at the most. The results also indicated that there are five most and five least strategies used by the respondents. This research is very useful as a reference in the framework of developing strategies for reading in tertiary institutions.